Programa de Erradicação do Trabalho Infantil (PETI) em Natal: uma avaliação na perspectiva da Assistência Social - Silva, Marisa Rodrigues da (2006)
This research deals with children and teenagers who are in childish work situation like juridical and institutional conquests connected with public politics in order to effects rights and social support about childish work eradication program (PETI) in terms of evaluation context under social work. The analysis of this research records the PETI implantation process at social nucleus in Cidade Nova (Natal/RN) to absorb children and teenagers who come from lixão . It does this based on the two thousands (2005) and presents the program importance linking users and their families such as the investigation of PETI actions, intending to give a contribution in the childish work combat and how they have been developed social-education protection for children and teenagers (seven to fifteens). About quality and quantity it was make a survey of social-economical characterization of the people benefits (to families) through interviews with users. This study (make us) sure brings new subventions which can cooperate to the childish work eradication by others public politics articulations